Kualitas Carbon Emission Disclosure Berdasarkan Gri 305 pada Laporan Keberlanjutan Perusahaan Sektor Tambang dan Properti Tahun 2020 – 2023: (Studi Multi Kasus Pada Negara : Indonesia, Jepang, Australia, Singapura, Austria) - Bondan Khoesnadi; Carmel Meiden (Jurnal Pengabdian Masyarakat, 2025)
This study aims to analyze the quality of carbon emission disclosure (CED) in the sustainability reports of mining and property sector companies, based on the Global Reporting Initiative (GRI) 305 standards. A multi-case study approach was applied to ten companies from Indonesia and developed countries (Japan, Australia, Singapore, Austria) covering the period 2020–2023. The method used is a descriptive quantitative and qualitative analysis, measuring compliance with seven GRI 305 indicators, including Scope 1, Scope 2, Scope 3, and additional indicators such as ozone-depleting substances and other air pollutants. The results show that only three out of ten companies demonstrate high disclosure quality. Most companies failed to adequately disclose Scope 3 and indicators GRI 305-6 and 305-7. Factors such as stakeholder pressure, national reporting systems, and internal corporate strategies significantly influence disclosure quality. This study emphasizes the need for stricter regulations and the active role of investors in promoting environmental transparency.